Moshe Bar Kepha's Cause of the celebration of the nativity: a genre for exegesis, ecumenism, and apology - Mušē Bar-Kēpā 813-903 (Texts from Christian late antiquity, 2017)
"This book is a part of series of Causes of Celebrations written by Moshe Bar Kepha (813-903). These Causes are unique in that they demonstrate a new genre of the Syriac literature initiated by the East Syriac authors at the beginning of the sixth century. Moreover, these Causes reveal the appreciation and dependency of Moshe Bar Kepha on the East Syriac sources despite the ecclesiastical doctrinal separation between the East Syriac and West Syriac churches. As a master of harmony of the Syriac literature, Moshe Bar Kepha adopts the early writing of the Cause of Nativity of the East Syriac author, Thomas of Edessa (d. 543), providing a masterpiece of hermeneutic theology and Christology for both East and West Syriac traditions. Moreover, he raised his exegetical studies to new heights of ecumenism, apology, and contextualization."--